Impact of Drain Usage on Postoperative Outcomes in Thyroidectomy Patients: Pain Intensity and Hospital Stay Duration - Kemal Duymaz, Yasar; Erkmen, Burak; Şahin, Şamil; Adnan Cırık, Ahmet; Çubuk, Hüseyin; Mahmut Tekin, Ahmet (ENT Updates, 2023)
Background: Thyroidectomy is a widely adopted surgical procedure for treating thyroid diseases. Despite its frequent application, postoperative complications like vocal cord paralysis, hypocalcemia, hematoma, and seroma can occur. A debate on the use of drains after thyroidectomy has persisted in the surgical community, with concerns about potential bleeding, occlusion, and the actual beneft of drains. Methods: A retrospective study was conducted on 122 patients who underwent thyroidectomy from January 2022 to May 2023. Patients were categorized into 2 groups: those with drains (n=62) and those without drains (n=60). Metrics like surgical duration, postoperative pain, length of hospital stay, and complications were recorded. A visual analog scale was employed to measure postoperative pain. Statistical analysis was performed using Statistical Package for the Social Sciences Statistics software, version 28.0. Results: There was no signifcant difference between the 2 groups in terms of age, gender, indication for surgery, and various complications. However, patients with drains experienced signifcantly higher pain scores on the frst postoperative day. Furthermore, the group with drains had a notably longer duration of hospital stay compared to the group without drains. Conclusion: Our fndings suggest that drain usage after thyroidectomy may intensify postoperative pain and extend hospital stays. Surgeons should meticulously evaluate the benefts and drawbacks of drain insertion in thyroidectomy procedures, as routine usage might be unnecessary.